Pengaruh Manajemen Laba Terhadap Nilai Perusahaan Dengan Corporate Governance Sebagai Variabel Moderasi (Studi Kasus Pada Perusahaan Goods Consumer yang Terdaftar di BEI) - Aditya Gede Pratama; Nasution, Yenni Samri Juliati; Nurwani (Journal Research of Economic and Bussiness, 2023)
This study aims to determine the effect of profit management on firm value with corporate governance as a moderating variable (a case study of consumer goods companies listed on the IDX for the 2018-2020 period). This study uses a quantitative method and an associative approach. The sample presentation technique uses purposive sampling with a data population of 61 companies which then becomes the sample of 14 companies for the 2018-2020 period. data collection techniques use documentation. Data analysis techniques using simple linear regression, moderation regression and hypothesis testing. The results of this study indicate that earnings management has an insignificant effect on firm value. Meanwhile, good corporate governance can to moderate the relationship between earnings management and firm value.